Powstanie Pięcioksięgu w świetle najnowszych badań - Rubinkiewicz, Ryszard (The Biblical Annals, 2017)
The paper shows the most important contemporary views on the origins of the Pentateuch. In the light of the most recent criticism, the traditional model of four sources of JEDP can no longer be held. Similarly, it is impossible to hold the early dates of the source (the tenth century BC) and the source E. Priority is given to the deuteronomic tradition formed in the 7th century BC, and then the Yahwistic J, or, as some prefer, the historical work made in Jerusalem (JG), and then the sacerdotal tradition. There is almost unanimous consent that the Pentateuch in its current form dates back to 400 BC.